PENGARUH PENGGUNAAN PAYLATER TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN DI APLIKASI SHOPEE - Stifani, Stifani; Rafida, Veni (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to analyze and explain the effect of using paylater from the convenience factor on customer satisfaction through purchasing decisions in the shopee application as a mediating variable. The type of research used is descriptive quantitative with a questionnaire data collection method. Sampling was done by purposive sampling method. The sample in this study were 100 respondents who had made transactions at Shopee using the Shopee pay later payment method. Data processing and analysis was carried out using path analysis with WarpPLS version 7 software. The results of this study are the ease of using paylater affects satisfaction, the use of paylater affects decisions, decisions affect satisfaction, and decisions are able to mediate the effect of using paylater on satisfaction.